Monoamine Oxidase-B Inhibitor Reduction in Pro-Inflammatory Cytokines Mediated by Inhibition of cAMP-PKA/EPAC Signaling - Putnins, Edward E.; Goebeler, Verena; Ostadkarampour, Mahyar (Frontiers in Pharmacology, 2021)
Mucosal epithelial cell integrity is an important component of innate immunity and it protects the host from an environment rich in microorganisms. Virulence factors from Gram-negative bacteria (e.g. lipopolysaccharide [LPS]) induce significant pro-inflammatory cytokine expression. Monoamine oxidase (MAO) inhibitors reduce cytokine expression in a variety of inflammatory models and may therefore have therapeutic potential for a number of inflammatory diseases. We tested the anti-inflammatory therapeutic potential of a recently developed reversible MAO-B inhibitor (RG0216) with reduced transport across the blood–brain barrier. In an epithelial cell culture model, RG0216 significantly decreased LPS-induced interleukin (IL)-6 and IL-1 gene and protein expression and was as effective as equimolar concentrations of deprenyl (an existing irreversible MAO-B inhibitor). Hydrogen peroxide and modulating dopamine receptor signaling had no effect on cytokine expression. We showed that LPS-induced expression of IL-6 and IL-1 was cAMP dependent, that IL-6 and IL-1 expression were induced by direct cAMP activation (forskolin) and that RG0216 and deprenyl effectively reduced cAMP-mediated cytokine expression. Targeted protein kinase A (PKA) and exchange protein activated by cAMP (EPAC) activation regulated IL-6 and IL-1 expression albeit in different ways but both cytokines were effectively decreased with RG0216. RG0216 reduction of LPS-induced cytokine expression occurred by acting downstream of the cAMP-PKA/EPAC signaling cascade. This represents a novel mechanism by which MAO-B selective inhibitors regulate LPS-induced IL-6 and IL-1 expression.